Religion as an Important Component of Diversity Religion in Counseling Training Programs / Robbie J. Steward, Matthew A. Miller and Alfiee Breland. - Steward, Robbie J. (Distributed by ERIC Clearinghouse, 1999)
This pilot study uses college faculty (n=10) and students (n=18) within American Psychological Association-approved department of counseling psychology programs to explore whether training programs are addressing religion as a component of diversity; how students with fundamental religious beliefs interact with members of their training program, both students and faculty, in the academic setting; and how students with fundamental religious beliefs are viewed within their training programs by students and faculty. Findings suggest that religion in general, and fundamentalist Bible-based beliefs specifically, are points of "uneasy" silence within the counseling training arena. This "uneasy" training program silence appears to mask strongly felt points of underlying contention among faculty, and among trainees, as well as between faculty and trainees. Many are choosing silence as a means of avoiding the assumed potential volatility that might ensue if discussion occurs. Fundamentalist trainees reported choosing silence to avoid penalty. In all silence, thought errors have the potential to flourish. Though the sample size is small, significant patterns were found that must be noted to better understand the impact of silence around religion on the climate within the training environment. An appendix provides comments from the faculty participants in response to survey items posted on the CCPTP listserv. (Contains 11 references and 6 tables.) (Author/MKA)